Studying the Relationship between Iris Diameter and Occlusal Vertical Dimension in Complete Denture Patients (Journal of Hama University, 2022)
Finding a reliable method for determining the correct occlusal vertical dimension is considered a major challenge to practitioners in complete removable prosthodontics. Several theories and beliefs have been developed about determining the occlusal vertical dimension as it was before edentulous situation. The eyeball reaches its full size at the age of 12 years. In a study, a relationship was found between the iris diameter and the width of the upper central incisor, therefore there may be a relationship between the iris diameter and the occlusal vertical dimension, which may provide a simple and precise technique for determining the occlusal vertical dimension in edentulous patients.The purpose of this research is to study the relationship between iris diameter and occlusal vertical dimension in people with natural teeth and in edentulous patients.The research sample consisted of 100 people with natural teeth (50 males and 50 females), and 20 edentulous patients (10 males and 10 females). The iris diameter and occlusal vertical dimension were measured and recorded for people with natural teeth and for edentulous patients using an electronic scale with an accuracy of 0.01 mm. The existence of a relationship between iris diameter and occlusal vertical dimension was studied in people with natural teeth and in edentulous patients, and the data were analyzed using Pearson's correlation coefficient analysis (P < .05).In the level of confidence of 95%, no statistically significant linear correlation was found between the iris diameter and the vertical occlusal dimension in the people with natural teeth and in the edentulous patients in the whole research sample, regardless of the sex of the patient.Within the limitations of the current study, we can say that there is no relationship between iris diameter and occlusal vertical dimension in people with natural teeth and in edentulous patients.